Perancangan Media Penelusuran Informasi Berbasis Website di Perpustakaan Unit Pelaksana Teknis Dinas Balai Diklat Koperasi (UPTD Balatkop) Provinsi Sumatera Barat - Herlinda, Trifani; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
This paper discusses about staking out of website based information investigation media in library of Unit Pelaksana Teknis Dinas (UPTD Balatkop) of west sumatera. This study is purposed for staking out of website as a information investigation media in library of UPTD Balatkop of west sumatera, with the result can be accessed by users as online. Staking out of website based information investigation media in library of UPTD Balatkop of west sumatera is dynamic, use Xammp as server local, Notepad++ for designing pages, PHP as language programmer and MySQL as database storage. Notepad++ is a language editor text and as editor of source code which is running in Windows operational system. Script code that used on notepad++ is PHP. This research is qualitative with deskriptif method. Data is collected by direct observation to the field research by observing information investigation that is used in library. Based on data analyzed, it can conclude that: (1) information investigation is a part of a process invention of information for user needs about information needed, by helping from any investigation tools and discoverer as having by information unit; (2) information investigation media in library of UPTD Balatkop of west sumatera just uses card catalog. In this time, the media for information investigate already sophisticated, that is website based investigation meia. But, it that library is not have yet media for information investigating that can be accessed in 24 hours by using own web. Keywords: Media Information Investigation and Website